Pengaruh Debt to Assets Ratio, Firm Size, Return on Assets dan Sales Growth Terhadap Price to Book Value - Intan Abriani Ayuningrum; Destina Paningrum; Anggit Dyah Kusumastuti (Universitas Sahid Surakarta, 2021)
The study aims to determine the effect of Debt to Assets Ratio (DAR), Firm Size,Return on Assets (ROA), and Sales Growth partially and simultaneously toward Price to Book Value (PBV) in food and beverage companies listed on the Indonesia Stock Exchange 2013-2017. The data are secondary data in the form of financial statements obtained through the website www.idx.co.id and Indonesian Capital Market Directory (ICMD) in 2013-2017. The sampling technique used a purosive sampling technique and involved 11 companies. The data analysis technique used multiple linier regression methods. The results indicate that Debt to Assets Ratio (DAR), Return on Assets (ROA), and Sales Growth have a significant partially effect toward Price to Book Value (PBV), while Firm Size does not significant partially influence toward Price to Book Value (PBV). Meanwhile Debt to Assets Ratio (DAR), Firm Size, Return on Assets (ROA), and Sales Growth have a significant simultaneously effect towards Price to Book Value (PBV) in food and beverage companies listed on the Indonesia Stock Exchange in 2012-2017.